A cultura de autoajuda: um olhar crítico a partir de Howard Clinebell - Cunha, Wadson Antonio da (2010)
The theme of self-help has invaded without reservation the lives of people in the actual world. This topic as a cultural offshoot of late modernity is present in literature, art, philosophy, political discussions and in business administration. It is present in the plurality of religion, in Christian theology, and the offices of psychologists and psychoanalysis. The huge cultural phenomenon does not limits itself to one segment, but according to our research, we will notice it is presence in various strata of society from the simplest on the outskirts of large cities to the rural residents in the corners of the world, reaching the middle class and apparently making the latter its promoter, partner and developer. Since the culture of self-help transits in the world of beliefs it is reasonable to assume that it is a phenomenon not only of psyco-physical nature, environmental or development and industrial production and technology, but also a metaphysical phenomenon. Self-help culture receives and borrows influences in the religious field. Self-help serves the purposes of philosophies that combine the expertise in some areas of psychophysical nature, management, medicine, and others with the transcendent experience coming from the most diverse religions and beliefs. There is a concern in the sense that this culture of self-help plays great role in the lives of the Christian communities that are replacing the pastoral counseling and pastoral care to these readings. The result of such readings is a movement towards individualism, secularism and plurality that are developed in the present age. This research will work with the hypothesis that Christian counseling is a better response to the expectation of the people of that culture of self-help. The theme of pastoral counseling will be approached based on the work of Howard Clinebell: Basic Types of Pastoral Care and Counseling: Resources for the Ministry of Healing and Growth. The first chapter will bring some definitions of self-help. It is expected that these definitions will bring the inputs to delineate an understanding of self-help. In order to support the understanding of self-help the chapter will point out also the origin of self-help literature, both from a historical point of view and ancient philosophical as well as its position in the rise in modern culture. This chapter will also address the self-help literature and its relation to individual autonomy. For this the texts of Francisco Ricardo Rüdiger: Self-Help and Individualism will be used. Chapter two will bring an introduction to Howard Clinebell, its methodology, its purpose in writing Basic Types of Pastoral Care and Counseling: Resources for the Ministry of Healing and Growth. We will present the actual challenge of pastoral care and pastoral counseling, and a holistic model focusing on healing and growth, as well as defining the work of the Christian counselor. We will also discuss the techniques used in pastoral counseling. The work environment of this ministry will also be identified. And finally this chapter will point out the care of the work of Christian counselor. In chapter three we will do a comparison of pastoral counseling according to Clinebell and the proposals of the culture of self-help within the concept of full life and the six dimensions of human completeness. At the conclusion, we plan to respond to our concern about the members of the Christian community and their use of self-help literature. We will also answer hypothesis that "the Christian counseling is a better response to the expectation of the people than that self-help culture / literature.